2012
DOI: 10.1155/2012/951272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Level Laser Stimulation on EEG

Abstract: Conventional laser stimulation at the acupoint can induce significant brain activation, and the activation is theoretically conveyed by the sensory afferents. Whether the insensible low-level Laser stimulation outside the acupoint could also evoke electroencephalographic (EEG) changes is not known. We designed a low-level laser array stimulator (6 pcs laser diode, wavelength 830 nm, output power 7 mW, and operation frequency 10 Hz) to deliver insensible laser stimulations to the palm. EEG activities before, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 33 publications
1
33
2
Order By: Relevance
“…Changes in the power of cortical rhythms can be influenced by the psychologic state, e.g., meditation can enhance the process of habituation to background stimuli (also acoustic, with no task imposed), and depression can reduce perception accuracy (13,14). Furthermore, we do not know what happens to cortical activity after the cessation of acoustic stimulation, e.g., EEG changes after conventional laser stimulation last for 15 minutes (15). To further investigate the usefulness of sound therapy for tinnitus, studies should be undertaken to observe neural activity on EEG and positron emission tomography simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the power of cortical rhythms can be influenced by the psychologic state, e.g., meditation can enhance the process of habituation to background stimuli (also acoustic, with no task imposed), and depression can reduce perception accuracy (13,14). Furthermore, we do not know what happens to cortical activity after the cessation of acoustic stimulation, e.g., EEG changes after conventional laser stimulation last for 15 minutes (15). To further investigate the usefulness of sound therapy for tinnitus, studies should be undertaken to observe neural activity on EEG and positron emission tomography simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Their brain waves changed. In particular, the α band increased in some regions, as shown in the lower right corner, and the β band decreased for normal subjects in the open eyes condition [7]. In this study, the conduction pathway was complicated, including nerve and meridian conduction.…”
Section: Methodsmentioning
confidence: 61%
“…LLL can induce the biophysical changes in many published papers. From our previous study, using LLL to radiate the left palm and observed with EEG, alpha (8-13Hz) activity increase in occipital, parietal, and temporal lobes, it showed the brain wave is influenced by LLL [7][8]. In this research, we use LED to replace LLL to radiate the palm and observe the brain wave change with EEG.…”
Section: Introductionmentioning
confidence: 88%